Barriers and Facilitators to DATA Waivered Providers Prescribing Buprenorphine: A Qualitative Analysis Applying the Theory of Planned Behavior. (15th October 2022) - Bapat, Shweta; Washburn, Micki; Tata, Vaishnavi; Fleming, Marc; Abughosh, Susan M.; Essien, E. James; Thornton, Douglas
Abstract: Background: Provider beliefs about the treatment of people with addiction may influence their prescribing behavior. Objective: This study applied the Theory of Planned Behavior (TPB), to identify the salient beliefs of Drug Addiction Treatment Act of 2000 (DATA 2000) waivered providers, concerning prescribing buprenorphine to patients with Opioid Use Disorder (OUD). Methods: Texas buprenorphine providers participated in one of four online focus group discussions conducted in fall 2019. The focus group discussion were audio recorded and the total length was between 60-90 minutes. Thematic analysis was conducted to identify emerging themes and to categorize the behavioral, normative, and control beliefs related to buprenorphine prescribing. Results: Of the 14 total participants, 57% of the participants were male and annually treated between zero to sixty patients with buprenorphine. The codes generated were represented in thematic maps, specifying the positive or negative aspects of buprenorphine prescribing. Results indicate that providers' primary motivation to prescribe buprenorphine was, implementation of a whole-patient approach through collaboration with behavioral health providers, in the provision of medications for opioid use disorder (MOUD). Providers primary normative belief was the recognition of key members of the medical community and patients' families and friends as influential groups. Providers' control beliefs focused on their ability to use buprenorphine in different practice settings. Conclusion: These results indicate that buprenorphine access may be expanded by increasing support for DATA waivered providers from other parts of the healthcare system such as behavioral health providers and pharmacists. Implications for clinical practice and future research will be discussed.